2021
DOI: 10.3389/fmicb.2021.743594
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Receptor Protein Positively Regulates the Expression of Genes Involved in the Biosynthesis of Klebsiella oxytoca Tilivalline Cytotoxin

Abstract: Klebsiella oxytoca is a resident of the human gut. However, certain K. oxytoca toxigenic strains exist that secrete the nonribosomal peptide tilivalline (TV) cytotoxin. TV is a pyrrolobenzodiazepine that causes antibiotic-associated hemorrhagic colitis (AAHC). The biosynthesis of TV is driven by enzymes encoded by the aroX and NRPS operons. In this study, we determined the effect of environmental signals such as carbon sources, osmolarity, and divalent cations on the transcription of both TV biosynthetic opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Interestingly, fecal tryptophan levels were reported to be decreased in preterm infants exposed to early antibiotics ( 64 ), and several studies suggest that antibiotic use in preterm infants increases the risk of NEC ( 65 , 66 ). Members of the K. oxytoca complex also utilize a broader array of sugars than other Klebsiella spp., which may provide the fermentative energy to support toxin production and promote colonization resistance of other enteric bacteria ( 67 , 68 ). Perturbations in the gut microbiome leading to excessive Toll-like receptor 4 (TLR4) stimulation have been suggested as an inciting event in NEC pathogenesis ( 69 , 70 ), whereas others have challenged the notion that NEC represents a single disease entity ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fecal tryptophan levels were reported to be decreased in preterm infants exposed to early antibiotics ( 64 ), and several studies suggest that antibiotic use in preterm infants increases the risk of NEC ( 65 , 66 ). Members of the K. oxytoca complex also utilize a broader array of sugars than other Klebsiella spp., which may provide the fermentative energy to support toxin production and promote colonization resistance of other enteric bacteria ( 67 , 68 ). Perturbations in the gut microbiome leading to excessive Toll-like receptor 4 (TLR4) stimulation have been suggested as an inciting event in NEC pathogenesis ( 69 , 70 ), whereas others have challenged the notion that NEC represents a single disease entity ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…We furthermore observed that glucose depletion and farnesol production by C. albicans induced increased P. mirabilis -mediated damage. Increased expression of virulence factors upon glucose deprivation has been described for different bacterial pathogens, including E. coli , Salmonella Typhi, Klebsiella oxytoca , and Yersinia pestis ( Jofre et al., 2014 ; Haycocks et al., 2015 ; Ritzert and Lathem, 2018 ; Rodriguez-Valverde et al., 2021 ). Cross-kingdom signaling properties of farnesol have been described for coinfections of C. albicans and Staphylocccus aureus where farnesol enhanced S. aureus biofilm formation and reduced staphyloxanthin production ( Kong et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Production and secretion of virulence factors in many bacterial pathogens are influenced by factors intrinsic to the host, the microenvironment, and the bacteria themselves. For example, the effect of the bacterial growth phase, the presence of carbon and nitrogen sources, salts, bile, hormones, pH, temperature, oxygen, and carbon dioxide may be important to trigger the expression of virulence genes in the host during infection or in extrahost environmental niches [23,[58][59][60][61][62][63]. In EPEC, the environmental and nutritional signals…”
Section: Discussionmentioning
confidence: 99%
“…Divalent cations such as Ca 2+ , Mg 2+ , and Mn 2+ are central to the stability and integrity of the cell membrane and are required in many cellular functions. Calcium and magnesium ions regulate virulence gene expression in E. coli, Klebsiella, Yersinia, and Salmonella species, respectively [60,62,[73][74][75]. In EPEC, the expression of BFP and translocated T3SSeffector proteins is also influenced by the presence of Ca 2+ and Mg 2+ salts in the growth media [49,51,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%